2003
DOI: 10.1053/jhep.2003.50034
|View full text |Cite
|
Sign up to set email alerts
|

Uroporphyria caused by ethanol in Hfe (−/−) mice as a model for porphyria cutanea tarda

Abstract: Two major risk factors for the development of porphyria cutanea tarda (PCT) are alcohol consumption and homozygosity for the C282Y mutation in the hereditary hemochromatosis gene (HFE). To develop an animal model, Hfe knockout mice were treated continuously with 10% ethanol in drinking water. By 4 months, uroporphyrin (URO) was detected in the urine. At 6 to 7 months, hepatic URO was increased and hepatic uroporphyrinogen decarboxylase (UROD) activity was decreased. Untreated Hfe(؊/؊) mice or wild-type mice tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Conventional models include exposure of cells to delta-aminolevulinate (ALA) for transient porphyria (42), chemical induction of hepatic porphyria (14), and random genetic mutations for producing porphyric mice (1,46), Saccharomyces cerevisiae (50), and zebra fish (49). Porphyria developed in these models is either of low level or not monospecific, thereby lacking sensitivity and specificity.…”
mentioning
confidence: 99%
“…Conventional models include exposure of cells to delta-aminolevulinate (ALA) for transient porphyria (42), chemical induction of hepatic porphyria (14), and random genetic mutations for producing porphyric mice (1,46), Saccharomyces cerevisiae (50), and zebra fish (49). Porphyria developed in these models is either of low level or not monospecific, thereby lacking sensitivity and specificity.…”
mentioning
confidence: 99%
“…l3 Histological grading was performed separately by two pathologists who agreed on the grading as described previously. 15 …”
mentioning
confidence: 99%
“…There are certainly complex interactions between HFE, iron, alcohol and UROD in the liver, as shown in the mouse HFE–/– model [36, 37]. Alcohol induces decreased activity of hepatic UROD in this model, which is mainly mediated by hepatic iron metabolism [36]. Another study also suggested a strong effect of the genetic background [37].…”
Section: Discussionmentioning
confidence: 99%
“…This unexpected finding suggests that there might be an interaction between HFE mutations and erythrocytic UROD. There are certainly complex interactions between HFE, iron, alcohol and UROD in the liver, as shown in the mouse HFE–/– model [36, 37]. Alcohol induces decreased activity of hepatic UROD in this model, which is mainly mediated by hepatic iron metabolism [36].…”
Section: Discussionmentioning
confidence: 99%